Association of Molnupiravir and Nirmatrelvir-Ritonavir with preventable mortality, hospital admissions and related avoidable healthcare system cost among high-risk patients with mild to moderate COVID-19 - Abraham Ka-Chung Wai; Crystal Ying Chan; Annie Wai-Ling Cheung; Kailu Wang; Sunny Ching-Long Chan; Teddy Tai-Loy Lee; Luke Yik-Fung Luk; Edmond Tsz-Fung Yip; Joshua Wing-Kei Ho; Omar Wai-Kiu Tsui; Kelly Wing-Yin Cheung; Shiyeow Lee; et al. (The Lancet Regional Health. Western Pacific, 2023)
Summary: Background: Real-world data is currently limited on the association between oral antiviral therapy and healthcare system burden in patients with mild-to-moderate COVID-19. This study aims to evaluate the clinical and cost effectiveness of Molnupiravir and Nirmatrelvir-ritonavir use in reducing mortality in this population. Methods: This is a retrospective cohort study involving 54,355 COVID-19 patients during February 22–March 31,2022 in Hong Kong. Inverse probability of treatment weighting (IPTW) was used to adjust patient characteristics. Our exposure of interest was Molnupiravir/Nirmatrelvir-Ritonavir prescription, with all-cause mortality as the primary outcome. IPTW-adjusted multivariate regressions were used to estimate treatment impact on clinic re-attendance and unplanned admissions. Finally, attributed cost and incremental cost-effectiveness ratios (ICER) were estimated. Findings: In the outpatient cohort (N = 33,217, 61.1%), 16.1% used Molnupiravir and 13.4% used Nirmatrelvir-Ritonavir, while in the inpatient cohort (N = 21,138, 38.9%), 3.8% used Molnupiravir and 1.3% used Nirmatrelvir-Ritonavir. IPTW-adjusted Cox model estimated that Molnupiravir (hazard ratio (HR)(95%CI)=0.31 (0.24-0.40), P< 0.0001) and Nirmatrelvir-Ritonavir (HR=0.10 (95%CI 0.05-0.21), P< 0.0001) were significantly associated with a reduced mortality hazard. In the outpatient cohort, both antiviral prescriptions were associated with reduced odds for unplanned hospital admissions (Molnupiravir: odds ratio (OR) =0.72 (0.52-0.98), P=0.039; Nirmatrelvir-Ritonavir: OR=0.37 (0.23-0.60), P<0.0001). Among hospitalised patients, both antiviral prescriptions were associated with significant reductions in the odds ratios for 28-days readmission (Molnupiravir: OR=0.71 (0.52-0.97), P=0.031; Nirmatrelvir-Ritonavir: OR=0.47 (0.24-0.93), P=0.030). ICERs for death averted for Molnupiravir stood at USD493,345.09 in outpatient settings and USD2,629.08 in inpatient settings. In outpatient settings, Nirmatrelvir-ritonavir cost USD331,105.27 to avert one death, but saved USD5,502.53 to avert one death in comparison with standard care. Interpretation: In high-risk patients in Hong Kong with mild-to-moderate COVID-19, Molnupiravir and Nirmatrelvir-Ritonavir prescriptions were associated with reduced all-cause mortality and significant cost savings. Funding: Centre for Health Systems & Policy Research is funded by The Tung's Foundation; and The Laboratory of Data Discovery for Health Limited(D24H) is funded the AIR@InnoHK platform administered by the Innovation and Technology Commission of Hong Kong. Funders did not have any role in study design, data collection, data analysis, interpretation and writing of this manuscript.